Synthesis, photophysical and photochemical properties of novel phthalocyanines substituted with triptycene moieties. (18th April 2015) - Ghanem, Bader S.; Pişkin, Mehmet; Durmuş, Mahmut; El-Khouly, Mohamed E.; Al-Raqa, Shaya Y.
Graphical abstract: New metal-free and zinc(II) phthalocyanines containing four triptycene moieties were synthesized for the first time. The photophysical and photochemical properties of the newly synthesized phthalocyanines were also investigated in tetrahydrofuran solution. Abstract: New metal-free and zinc(II) phthalocyanines containing four triptycene moieties were synthesized and characterized by 1 H NMR, mass, IR, electronic spectroscopies and elemental analysis as well. The steady-state absorption spectra of the investigated compounds exhibited the main absorption bands in the visible region, at around 700 nm. The fluorescence spectra and quantum yields were recorded by steady-state emission measurements. The powerful nanosecond laser flash photolysis technique was employed to record the transient absorption spectra of the long-lived triplet states of the investigated compounds. The singlet oxygen generation and photodegradation properties of the target phthalocyanines under light irradiation were also investigated in tetrahydrofuran solution.